How is the value of the exhibition brand in the eyes of the audience? Based on the perspective of green practice - Jia, Pengshe; Tang, Ying; Du, Yunqian (Frontiers in Psychology, 2022)
Studies have found that green practices can help organization create unique competitive advantages, such as enhancing the brand value. However, in the existing research, people did not know much about the exhibition audiences’ perceptions of green practices, or its impact on brand loyalty. This study explores the dimension of green practice perceptions of exhibition audiences, uses the trust-commitment theory to verify the relationship between green practice perceptions and exhibition brand loyalty. A total of 665 valid questionnaires were collected in the two exhibitions. The results show that four of the five types of green practices perceived by the audience will significantly affect green trust and then brand loyalty through commitment. Two of the five types of green practice perception can directly affect brand loyalty. And green self-identity will significantly adjust the relationship between green trust and affective commitment. Finally, suggestions are proposed for academic and practical reference.